2012
DOI: 10.1074/jbc.m112.374322
|View full text |Cite
|
Sign up to set email alerts
|

Rabex-5 Protein Regulates the Endocytic Trafficking Pathway of Ubiquitinated Neural Cell Adhesion Molecule L1

Abstract: Background:The endocytic trafficking pathway for L1 proteolytic degradation following L1-L1 homophilic binding remains unclear.Results: Changes in Rabex-5 expression alter the dynamics of ubiquitinated L1 endocytic trafficking. Conclusion: Rabex-5 has an essential role in the endocytic trafficking of ubiquitinated L1. Significance: The motif interacting with ubiquitin (MIU) domain, not the A20 ZnF domain, in Rabex-5 controls the endocytic trafficking of ubiquitinated cargo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…Rabex-5, EHD1/4, EEA1) have been implied in L1 surface recycling (Aikawa, 2012;Yap et al, 2010;Lasiecka et al, 2014). For example, the surface expression of L1 is increased in dendrites of EHD1-overexpressing neurons (Yap et al, 2010).…”
Section: Sara Regulates the Surface Expression Of L1mentioning
confidence: 99%
“…Rabex-5, EHD1/4, EEA1) have been implied in L1 surface recycling (Aikawa, 2012;Yap et al, 2010;Lasiecka et al, 2014). For example, the surface expression of L1 is increased in dendrites of EHD1-overexpressing neurons (Yap et al, 2010).…”
Section: Sara Regulates the Surface Expression Of L1mentioning
confidence: 99%
“…To exert Ub-ligase activity, the A20-ZnF domain binds Ub-charged Ubc5 (an E2 enzyme) in a manner that depends upon the residues involved in Ub binding. In a previous study, we reported that the MIU domain, rather than the A20-ZnF domain, is specifically involved in the trafficking of ubiquitinated cargo into endosomes via a direct interaction (18). Our findings thus suggested that the MIU and A20-ZnF domains are functionally distinct in the Ub signaling pathways.…”
mentioning
confidence: 76%
“…Cell Culture, Transfection, and DNA Constructs-Mouse neuroblastoma N2a cells and human embryonic kidney 293T (HEK293T) cells were cultured and transfected by using Lipofectamine 2000 (Invitrogen) as described previously (18). The human Rab5a construct was amplified using PCR from cDNA and subcloned into an EGFP-N1 vector.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations